Penegakan Sanksi Hukum Kepada Penyelenggara Pemilihan Kepala Daerah Yang Mempengaruhi Pemilih - Maupiku, Viantrus; Mustamu, Julista; Lekipiouw, Sherlock Halmes (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The oath/promise of the Provincial KPU, Regency/Municipal KPU members in carrying out their duties and authorities will work sincerely, honestly, fairly, and carefully for the success of the General Election and the establishment of democracy and justice, as well as prioritizing the interests of the Unitary State of the Republic of Indonesia over personal or group interests.Purposes of the Research: This writing aims to identify and analyze the enforcement of legal sanctions for Regency KPUs that are proven to influence voters in the regional head election process. Methods of the Research: The research method used is normative juridical research with descriptive analytical research. The problem approach used is a legal approach and a conceptual approach. The sources of legal materials used are primary legal materials and secondary legal materials. The collection technique is through a literature study, then the legal materials collected are then analyzed qualitatively.Results of the Research: The results of the study indicate that the enforcement of administrative legal sanctions against Jakob Alupatti Demny as the Head of MBD Regency KPU is in accordance with the provisions of Article 27 paragraph (2) of Law Number 15 of 2011 concerning Election Organizers which explains that members of KPU Regency KPU, Provincial KPU, and Regency KPU The city is dishonorably dismissed if it violates the oath/promise of office and/or the code of ethics. However, until now Jakob Alupatti Demny is still a member of the MBD Regency KPU.